Influence of water masses and environmental variables on fish community in the south bank of Yangtze River Estuary, China - Dongrong Zhang; Dongrong Zhang; Hengtao Xu; Hengtao Xu; Xin Fang; Xin Fang; Wei Huang; Wei Huang; Youzheng Zhang; Youzheng Zhang; Jian Qian; Jian Qian (Frontiers in Marine Science)
Fish play a crucial role in the estuarine ecosystem due to their ecological and commercial significance. Consequently, it is essential to study the characteristics of fish communities and their impacts within the estuary. In this study, we employed a single-boat bottom trawl to conduct four fishery resource surveys in April (spring), August (summer), October (autumn), and December (winter) of 2020 at ten sampling sites along the south bank of the Yangtze River Estuary (SBYRE). The primary objective was to assess the influence of water masses and environmental variables on the spatial and temporal distribution and diversity of fish communities in the SBYRE. The results indicated that fish biomass and abundance during summer were significantly higher than those observed in the other three seasons. High-value areas were predominantly located on the nearshore of the SBYRE and the north bank of Hangzhou Bay, a finding also corroborated by the cluster heat map results. Furthermore, the environmental variables in summer differed significantly from those in the other seasons, suggesting that the temporal and spatial distribution of fish was substantially influenced by these variables during the summer months. Mantel test and redundancy analysis demonstrated a positive correlation between the biomass and abundance of fish in summer and the factors of temperature and salinity. The seasonal alternation of dominant fish species contributes significantly to the heterogeneity observed in the temporal and spatial distribution of their communities. The reduced biomass and abundance of fish in spring were attributed to the lower influx of freshwater from the upstream. Seasonal variations in the fronts created by the confluence of multiple water masses in the study area, which play a crucial role in influencing the temporal and spatial distribution of fish communities. Furthermore, the presence of these fronts provides suitable habitats for spawning, feeding, and fattening for various fish species, making them ideal environments for numerous migratory fish. This study enhances our understanding of the temporal and spatial heterogeneity of fish communities in estuarine ecosystems and the factors influencing them, offering valuable insights for the protection and restoration of estuarine marine ecosystems.